Understanding work and study demands of degree apprentices using conservation of resources theory - Sally Smith; Ella Taylor-Smith; Andrew Bratton; Matthew Dutton (Empirical Research in Vocational Education and Training)
Abstract Degree apprenticeships are a recent innovation in the UK. The overarching goal of the apprenticeship is to achieve a degree, while working and advancing careers. This involves apprentices and employing organisations investing in resources including workplace support for education and new skills. This study interviewed apprentices (n = 28) approaching the completion of their apprenticeship (and degree) to explore this investment through the lens of Conservation of Resources Theory; specifically, whether apprentices had achieved their goals and how they had managed the challenges of balancing work, life, and study. This unique approach considered how apprentices gained and conserved resources conducive to reducing workplace stress, to gain insights into apprentices’ experiences, resulting in a new resource model for apprenticeships. Goals achieved included the degree award, promotions, pay rises and increased status. We found that skills acquisition, alignment of work/ study, and high levels of support increased the apprentices’ resources. Workplace mentors had a crucial role to play, but their approach varied widely, indicating that improving key features of apprenticeship implementation could conserve apprentices’ resources, enhancing apprentice wellbeing. The significance of the findings is a new resource model for understanding the intersection of work and study.